Fishing-Injury-Related Flexor Tenosynovitis of the Hand: A Case Report and Review - Danny A. Young-Afat; Deniz Dayicioglu; John C. Oeltjen; Audene P. Garrison (Case Reports in Orthopedics)
Hand infections occurring after fishing and other marine-related activities may involve uncommon bacteria that are not susceptible to the conventional or empiric antibiotic therapy used to treat soft tissue infections. Therefore appropriate treatment is often delayed and could lead to severe hand damage. An illustrative case of fishing-related injury leading to complicated tenosynovitis and horseshoe abscess caused by Mycobacterium marinum and its treatment course is outlined. Laceration of the skin during boating is fairly common. Because of the rarity of some of the bacteria, referrals to the appropriate specialist including hand surgeons and infectious disease specialists should occur in early stages. M. marinum infections should always be considered in injuries related to seawater and fishing as this may lead to early appropriate treatment and prevent severe damage.